The impact of cognitive factors on individuals' financial decisions / Marhanum Che Mohd Salleh ... [et al.] - Che Mohd Salleh, Marhanum; Chowdhurya, Mohammad Abdul Matin; Mohd Nasarudina, Ahmad Fawwaz; Ratnasarib, Ririn Tri (Universiti Teknologi MARA, Shah Alam: Accounting Research Institute (ARI), 2020)
The objective of this paper is to examine the effect of cognitive factors which are financial knowledge, herding behaviour and financial planning towards individuals' financial decisions. A total of 173 survey data were collected from university staff consisting of administrative and academic members. This research adopted a quantitative methodology for data collection as well as data analysis. Multiple regression analysis was used to examine the effect of cognitive factors towards the dependent variable which is financial decision. Results indicate that only two cognitive variables which are financial knowledge and financial planning have a significant effect toward financial decisions. Herding behaviour was found to insignificantly effect the individual financial decision process. Results of this research would be of significance to proof that other than external factors, internal factors which are cognitive elements are crucial in influencing individual financial decisions.